Pengaruh Pola Asuh Orang Tua Dalam Pembentukan Karakter Disiplin Pada Anak Dalam Lingkungan Keluarga - I Ketut Rindawan; I Made Purana; Fransiska Kamilia Siham (Universitas Pendidikan Ganesha, 2020)
The parenting style of the parents has a very big influence on the formation of the child's personality. This pattern of behavior is immediately felt by children, be it positive behavior or negative behavior. Character are the values of human behavior related to God Almighty, self, fellow human beings, the environment, and nationality which are manifested in thoughts, attitudes, feelings, words, and actions based on religious norms, law, karma, culture. , and customs. Based on this fact, the researcher wanted to examine the influence of parenting styles in the formation of disciplinary characters in children in the family environment in Wae Kelambu, Komodo Manggarai Barat sub-district. This study aims to determine the influence of parenting styles in the formation of disciplinary characters in children in the family environment. This type of research is descriptive using a qualitative approach, the research subjects are some parents who practice parenting. The techniques used in writing scientific papers are observation techniques and interview techniques. The data were analyzed descriptively qualitatively. Parenting patterns play an important role in fostering the development of children's character. In the Wae Kelambu sub-district, Komodo Manggrai Barat Subdistrict, West Manggrai, East Nusa Tenggara adopts authoritarian parenting, democratic parenting, and permissive parenting. A decision is made jointly by considering both parties. Children are given the freedom to be responsible, which means that what the children do must still be under the supervision of their parents and can be morally responsible. Suggestions for planting good characters in this research site are at least maintained and maximally improved.